Prevention and Eradication of Biofilm by Dendrimers: A Possibility Still Little Explored - Silvana Alfei; Debora Caviglia (MDPI AG, 2022)
Multidrug resistance (MDR) among pathogens and the associated infections represent an escalating global public health problem that translates into raised mortality and healthcare costs. MDR bacteria, with both intrinsic abilities to resist antibiotics treatments and capabilities to transmit genetic material coding for further resistance to other bacteria, dramatically decrease the number of available effective antibiotics, especially in nosocomial environments. Moreover, the capability of several bacterial species to form biofilms (BFs) is an added alarming mechanism through which resistance develops. BF, made of bacterial communities organized and incorporated into an extracellular polymeric matrix, self-produced by bacteria, provides protection from the antibiotics' action, resulting in the antibiotic being ineffective. By adhering to living or abiotic surfaces present both in the environment and in the healthcare setting, BF causes the onset of difficult-to-eradicate infections, since it is difficult to prevent its formation and even more difficult to promote its disintegration. Inspired by natural antimicrobial peptides (NAMPs) acting as membrane disruptors, with a low tendency to develop resistance and demonstrated antibiofilm potentialities, cationic polymers and dendrimers, with similar or even higher potency than NAMPs and with low toxicity, have been developed, some of which have shown in vitro antibiofilm activity. Here, aiming to incite further development of new antibacterial agents capable of inhibiting BF formation and dispersing mature BF, we review all dendrimers developed to this end in the last fifteen years. The extension of the knowledge about these still little-explored materials could be a successful approach to find effective weapons for treating chronic infections and biomaterial-associated infections (BAIs) sustained by BF-producing MDR bacteria.